Nutritional evaluation of hominy as poultry feed - Kompiang, I Putu; ., Supriyati (Indonesian Journal of Animal and Veterinary Sciences, 1998)
A series of chemical, biological assay and growth trials were conducted to determine the nutritive value of hominy, relative to corn. The crude protein, ash, NDF and ADF content of hominy were 10.25%, 2.10%, 19.10% and 4.70% respectively, and are higher than the corn level, 8.5%, 0.40%, 2.30% and 1.90% respectively. While its crude fat (3.20%) and metabolize energy (3,020 kcal/kg) contents were lower than the corn level 4,40% and 330 kcal/kg. Seven hundred DOC broilers of commercial strain were used for growth trial for 42 days. The birds were divided into 5 treatments group with 4 replications (35 bird/replicate). Experimental rations, starter and finisher, were formulated with graded levels of hominy on the expense of corn (A = 0%, B = 33.3%, C = 50%, D= 66.6% and E = 100%) with similar level of crude protein and metabolize energy. Feed consumption was not affected (P>0.05) by the treatments, however body weight gain (BWG) and feed conversion ratio (FCR) were both significantly (P<0.05) affected by the treatments. Body weight gain of treatment A (1,712 g) was similar to treatment B (1,683 g) and C (1,682 g) but significantly (P<0.05) higher than treatment D (1,598 g) and E (1,570 g). Feed convertion ratio of treatment A (2.17) was similar to the treatment B (2.26) but significantly better (P<0.05) than treatment C (2.30), D (2.36) and E (2.39). Carcass quality was not affected by the treatments except for the shank color, where treatment A (7.38) was significantly yellower than the other treatments (B=2.50, C=2.75, D=1.75 and E=1.0). It is concluded that the protein content of hominy is higher than corn, but its metabolize energy was lower than the corn. Hominy could be included in the ration replacing corn up to 33.3% without affecting performance of the bird. Â  Key words : Poultry, hominy, nutrient